Interpretation Analysis of Educational Values in the Anime Ansatsu Kyoushitsu (Assasination Classroom) - Dewi, Hamidah Nurifah; Aggasi, Abbyzar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Anime Ansatsu Kyoushitsu is an anime in the genre of action, comedy, drama and school, released in 2012 by Yusei Matsui. It tells the story of Kunugigaoka middle school, which is called the outcast class. This research aims to find out how character education can affect students in the school environment, and how to analyze the content of the story message using Ferdinand De Saussure's theory. This type of research is a type of qualitative research to obtain in-depth and meaningful data and uses data collection techniques in the form of literature studies that collect reading materials, library data, and others as references. This research is expected to provide an understanding of education, especially character education, and to dig deeper into the meaning and purpose of semiotics. Saussure's semiotics focuses on the relationship between signifier and signified based on an agreement called meaning. Based on the analysis of the anime Ansatsu Kyoushitsu, there are several character applications that can be applied in everyday life, namely responsibility, empathy, discipline, courage, cooperation, creativity and appreciation of students. In addition, it can be concluded that the anime tells the story of how a teacher should be a role model and inspirational for students. Teaches the importance of instilling character education in students.